Analysis of electronic government implementation in Tamalate District, Makassar City - Surfian Rahmat; Muh. Zacky Radwa Alfaridzi (Department of Government Science, 2025)
This study examines the implementation of e-government principles and the conditions of e-government success factors in Tamalate District, Makassar City. A qualitative research methodology was employed, utilizing observation, interviews, literature review, and documentation for data collection. Both primary and secondary data were analyzed through data reduction, presentation, verification, and conclusion drawing processes. Results indicate that e-government principles enforcement and success factor achievement remain below ideal standards. Key principles, including transparency, accessibility, efficiency, effectiveness, and information security face significant obstacles. Transparency implementation remains incomplete, public accessibility is limited, system deployment is partial, and information security measures are inadequate. The critical success factors—human resources and ICT infrastructure—also present challenges. Employee capabilities in operating e-government systems are inconsistent, and preventive measures against ICT equipment damage are insufficient for maintaining reliable electronic government operations. This study concludes that e-government implementation in Tamalate District requires substantial improvement across all dimensions. Comprehensive reforms targeting these identified weaknesses, the district's electronic government system will continue operating below its potential effectiveness in serving public needs.